2024
DOI: 10.1021/acs.inorgchem.3c03941
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Eu-Based MOF Luminescence Sensor for Clenbuterol Visible Recognition

Xudong Zhang,
Wenyu Ding,
Chuanbao Jiao
et al.

Abstract: Clenbuterol (CLB) as an illegal feed additive may cause a great security risk to food safety. However, convenient and efficient detection means for CLB in practical application remain a formidable challenge. Herein, a stable Eu-based organic framework {[H2N­(CH3)2]2[Eu2(ttca)2]·H2O}n (compound 1) (H4ttca = [1,1′:2′,1″-terphenyl]-4,4′,4″,5′-tetracarboxylic acid) has been harvested, exhibiting excellent chemical stability and thermal stability. Luminescence investigation reveals that compound 1 can sensitively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Herein, a butterfly shaped aromatic tetracarboxylic ligand [1,1′:2′,1″-terphenyl]-4,4′,4″,5-tetracarboxylic acid (H 4 TTCA) was selected to prepare a Cd-based MOF (Cd 2 (TTCA)­(H 2 O) 4 ·H 2 O, denoted as TTCA-Cd), owing to its abundant coordination sites, rich coordination modes, and aromatic character, which are favorable to the stability of MOFs. , For the purpose of developing a ratiometric probe, a Tb­(III) ion was introduced in this MOF by the solvothermal method, and the obtained TTCA-Cd@Tb displayed not only the ligand-centered emission but also the typical emissions of Tb­(III). It was revealed that it could be used as a rational fluorescence probe of DPA with a very low LOD of 7.14 nM, a large detecting range (0–200 μM), and high selectivity, which is a promising DPA fluorescent probe (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, a butterfly shaped aromatic tetracarboxylic ligand [1,1′:2′,1″-terphenyl]-4,4′,4″,5-tetracarboxylic acid (H 4 TTCA) was selected to prepare a Cd-based MOF (Cd 2 (TTCA)­(H 2 O) 4 ·H 2 O, denoted as TTCA-Cd), owing to its abundant coordination sites, rich coordination modes, and aromatic character, which are favorable to the stability of MOFs. , For the purpose of developing a ratiometric probe, a Tb­(III) ion was introduced in this MOF by the solvothermal method, and the obtained TTCA-Cd@Tb displayed not only the ligand-centered emission but also the typical emissions of Tb­(III). It was revealed that it could be used as a rational fluorescence probe of DPA with a very low LOD of 7.14 nM, a large detecting range (0–200 μM), and high selectivity, which is a promising DPA fluorescent probe (Scheme ).…”
Section: Introductionmentioning
confidence: 99%